Optimization of a Modified QuEChERS Method of Experimental Design for Vitamin B2, B3, B6 and B9 in Powder Formula Milk by HPLC/DAD - Thi, Ngoc-Van Nguyen; Duong, Ngan Tuyet; Pham, Thanh Tuan; Duong, Chau Ngoc; Thi, Cam-Thuy Le; Pham, Kieu Bich; Nguyen, Kien Trung (Science and Technology Indonesia, 2024)
The purpose of this work is to use HPLC/DAD to ascertain the best extraction and cleanup conditions for various forms of vitamin B in powder formula milk. The QuEChERS method’s key variables were optimized using a Box-Behnken design with 3-level 4-variable and Minimum-Run Resolution IV Screening Design. Following the selection of the best experimental setup, the suggested approach was applied to quantify four vitamins B (B2, B3, B6, and B9) in powder formula milk matrix by HPLC/PDA in accordance with AOAC and ICH guidelines. When taking into account the performance standards given in this guideline, the approach presented recovery between 83.55 and 108.43 for 4 B vitamins, which is adequate. The intra-day and inter day percentage relative standard deviations were 1.66 to 2.75% and 0.47 to 4.78%, respectively. Furthermore, the technique enabled the determination of low detection limits in less than 25 minutes of analytical time. The proposed method’s excellent accuracy, precision, and efficiency made it acceptable for regular B vitamin analysis when applied to powder formula milk samples. The findings confirmed that the modified QuEChERS technique is appropriate for routinely assessing B vitamin levels in powder formula milk matrix.